Heterogeneous Implementation of Preconditioners Based on Gauss–Seidel Method for Sparse Block Matrices - Magomedov, A. R.; Gorobets, A. V. (Computational mathematics and modeling, 2022)
In this paper we present a parallel preconditioner algorithm for the Krylov-type iterative method based on the multicolor Gauss–Seidel method and its transferable heterogeneous software implementation using the OpenCL computational standard. A special feature is its application to block sparse matrices as part of a numerical technique for modeling compressible turbulent flows. Optimization techniques are described that allow obtaining multiple speedups on graphics processors. Results of performance testing on a hybrid computing system are presented.